Salivary cortisol, dehydroepiandrosterone, and chromogranin A levels in patients with gingivitis and periodontitis and a novel biomarker for psychological stress - Lee, Yeon-Hee; Suk, Chon; Shin, Seung-Il; Hong, Ji-Youn (Frontiers in Endocrinology, 2023)
Aim: The purpose of this study was to investigate the neuroendocrine responses, which reflect the activity of the hypothalamic-pituitary-adrenal axis, according to the presence or absence of psychological stress in patients with gingivitis and periodontitis compared to healthy controls. Methods: In total, 117 patients (60 women, mean age:36.29 ± 19.03 years) participated in this cross-sectional study, consisting of 32 healthy controls, 49 patients with gingivitis, and 36 patients with periodontitis. The presence of psychological stress and salivary characteristics were investigated, and the stress-related biomarkers of cortisol, DHEA, cortisol/DHEA ratio, and chromogranin A in saliva were analyzed. Results: The levels of salivary cortisol and chromogranin A increased with the severity of periodontal disease, being the highest in the periodontitis group and statistically significantly higher in the order of periodontitis, gingivitis, and healthy control groups (all p < 0.001). In addition, the levels of DHEA and cortisol/DHEA ratio were higher in the periodontitis group than in the healthy control group (all p < 0.001). A multivariate logistic regression analysis revealed that the factors predicting above-average values of cortisol were periodontitis (odds ratio [OR] = 256.829, p < 0.001), women (OR = 6.365, p = 0.004), and psychological stress (OR=6.036, p = 0.007); of cortisol/DHEA ratio were periodontitis (OR = 11.436, p < 0.001), psychological stress (OR = 3.977, p = 0.003), and women (OR = 2.890, p = 0.026). Thus, periodontitis and psychological stress were significant and strong predictors of above-average cortisol and cortisol/DHEA ratio values. In the gingivitis group, salivary cortisol (r = 0.381, p = 0.007) and cortisol/DHEA ratio (r = 0.479, p < 0.001) levels correlated with the presence of psychological stress. In the periodontitis group, increased cortisol/DHEA ratio (r = 0.412, p = 0.013) and lowered salivary buffer capacity (r = -0.334, p = 0.047) correlated with the presence of psychological stress. Conclusion: We observed differences in the levels of stress-related neuroendocrine parameters by periodontal disease severity. Novel biomarkers for periodontitis severity could be salivary cortisol and chromogranin A. Above-average cortisol and cortisol/DHEA ratio values can be significant predictors of psychological stress in patients with gingivitis and periodontitis.